1997
DOI: 10.1128/jcm.35.1.223-227.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection and sequences of the enteroaggregative Escherichia coli heat-stable enterotoxin 1 gene in enterotoxigenic E. coli strains isolated from piglets and calves with diarrhea

Abstract: Enterotoxigenic Escherichia coli (ETEC) strains isolated from piglets and calves with diarrhea were tested for the presence of the enteroaggregative E. coli enterotoxin 1 (EAST1) gene sequences by PCR and colony hybridization. The EAST1 gene was found in most porcine ETEC strains with adherence factor K88, especially in those elaborating heat-labile enterotoxin. One porcine ETEC strain with adherence factor K99 was also positive for the EAST1 gene. In contrast, 987P-positive (987P ؉) ETEC strains from piglets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…The gene (astA) encoding the production of EAST1, a plasmidencoded enterotoxin, has been detected in several groups of diarrhoeagenic E. coli (EAEC (Enteroaggregative Escherichia coli), EPEC, ETEC and STEC (Shiga toxinproducing Escherichia coli)) isolated from humans and pigs. The pathogenic significance of EAST1 in diarrhoea in pigs is not known (Yamamoto and Nakazawa 1997;Choi et al 2001;Frydendahl 2002;Noamani et al 2003;Osek 2003). Of note is also that the gene iss (involved in serum resistance), usually associated with poultry disease and suggested to be a gene used to separate chicken isolates from the majority of isolates from mammalian sources (David et al 2010) was found in 14 different profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The gene (astA) encoding the production of EAST1, a plasmidencoded enterotoxin, has been detected in several groups of diarrhoeagenic E. coli (EAEC (Enteroaggregative Escherichia coli), EPEC, ETEC and STEC (Shiga toxinproducing Escherichia coli)) isolated from humans and pigs. The pathogenic significance of EAST1 in diarrhoea in pigs is not known (Yamamoto and Nakazawa 1997;Choi et al 2001;Frydendahl 2002;Noamani et al 2003;Osek 2003). Of note is also that the gene iss (involved in serum resistance), usually associated with poultry disease and suggested to be a gene used to separate chicken isolates from the majority of isolates from mammalian sources (David et al 2010) was found in 14 different profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to STa and STb, the 38 amino acid EAST1 toxin is less well characterized both in terms of function and contribution to ETEC-mediated disease. While EAST1 was originally isolated from EAEC strain 17-2, it has now been identified in other pathotypes of E. coli including ETEC strains from human and animal sources (Yamamoto & Echeverria, 1996;Yamamoto & Nakazawa, 1997;Veilleux & Dubreuil, 2006). However, the role of EAST1 in mediating diarrhoea remains controversial; while several epidemiological studies have implicated the toxin in mediating disease (Menard & Dubreuil, 2002;Veilleux & Dubreuil, 2006), EAEC strain 17-2 failed to elicit diarrhoea in human volunteer studies (Nataro et al, 1995).…”
Section: East1 a Novel Heat-stable Enterotoxinmentioning
confidence: 99%
“…Multiplex PCR using published primers (Appendix 1 [8][9][10][11][12][13][14][15] ) was performed in a total reaction volume of 50 mL (Master mix -12.5 mL, reverse and forward oligonucliotide primers -50 pmol, and boiled suspension as template DNA -6.0 mL). The amplification was performed in thermal mini cycler (M. J.…”
Section: Detection Of Diarrhoeagenic E Coli By Polymerase Chain Reacmentioning
confidence: 99%